Berberine improves glucose metabolism in diabetic rats by inhibition of hepatic gluconeogenesis. - Xuan Xia; Jinhua Yan; Yunfeng Shen; Kuanxiao Tang; Jun Yin; Yanhua Zhang; Dongjie Yang; Hua Liang; Jianping Ye; Jianping Weng (PLoS ONE)
Berberine (BBR) is a compound originally identified in a Chinese herbal medicine Huanglian (Coptis chinensis French). It improves glucose metabolism in type 2 diabetic patients. The mechanisms involve in activation of adenosine monophosphate activated protein kinase (AMPK) and improvement of insulin sensitivity. However, it is not clear if BBR reduces blood glucose through other mechanism. In this study, we addressed this issue by examining liver response to BBR in diabetic rats, in which hyperglycemia was induced in Sprague-Dawley rats by high fat diet. We observed that BBR decreased fasting glucose significantly. Gluconeogenic genes, Phosphoenolpyruvate carboxykinase (PEPCK) and Glucose-6-phosphatase (G6Pase), were decreased in liver by BBR. Hepatic steatosis was also reduced by BBR and expression of fatty acid synthase (FAS) was inhibited in liver. Activities of transcription factors including Forkhead transcription factor O1 (FoxO1), sterol regulatory element-binding protein 1c (SREBP1) and carbohydrate responsive element-binding protein (ChREBP) were decreased. Insulin signaling pathway was not altered in the liver. In cultured hepatocytes, BBR inhibited oxygen consumption and reduced intracellular adenosine triphosphate (ATP) level. The data suggest that BBR improves fasting blood glucose by direct inhibition of gluconeogenesis in liver. This activity is not dependent on insulin action. The gluconeogenic inhibition is likely a result of mitochondria inhibition by BBR. The observation supports that BBR improves glucose metabolism through an insulin-independent pathway.